Calreticulin Mutations in Myeloproliferative Neoplasms: Comparison of Three Diagnostic Methods. - Ji-Hye Park; Margaux Sevin; Selim Ramla; Aurélie Truffot; Tiffany Verrier; Dominique Bouchot; Martine Courtois; Mathilde Bas; Sonia Benali; François Bailly; Bernardine Favre; Julien Guy; et al. (PLoS ONE, 2015)
Calreticulin (CALR) mutations have recently been reported in 70-84% of JAK2V617F-negative myeloproliferative neoplasms (MPN), and this detection has become necessary to improve the diagnosis of MPN. In a large single-centre cohort of 298 patients suffering from Essential Thrombocythemia (ET), the JAK2V617F, CALR and MPL mutations were noted in 179 (60%), 56 (18.5%) and 13 (4.5%) respectively. For the detection of the CALR mutations, three methods were compared in parallel: high-resolution melting-curve analysis (HRM), product-sizing analysis and Sanger sequencing. The sensitivity for the HRM, product-sizing analysis and Sanger sequencing was 96.4%, 98.2% and 89.3% respectively, whereas the specificity was 96.3%, 100% and 100%. In our cohort, the product-sizing analysis was the most sensitive method and was the easiest to interpret, while the HRM was sometimes difficult to interpret. In contrast, when large series of samples were tested, HRM provided results more quickly than did the other methods, which required more time. Finally, the sequencing method, which is the reference method, had the lowest sensitivity but can be used to describe the type of mutation precisely. Altogether, our results suggest that in routine laboratory practice, product-sizing analysis is globally similar to HRM for the detection of CALR mutations, and that both may be used as first-line screening tests. If the results are positive, Sanger sequencing can be used to confirm the mutation and to determine its type. Product-sizing analysis provides sensitive and specific results, moreover, with the quantitative measurement of CALR, which might be useful to monitor specific treatments.